Reaching Out: Supporting Families and Carers Bereaved During COVID-19 - Barbara von Barsewisch; Su Yin Yap; Bernie Byrne (Archives of Nursing Practice and Care - Peertechz Publications, 2020)
The past few months of responding to COVID-19 were undoubtedly a challenging time. The North Middlesex University Hospital in North London experienced an early peak of deaths from Covid-19. With no visiting allowed to keeo the footfall through the hospital as low as possible, patients and their families were unable to share the final days or hours and were unable to say goodbye. In response, Su Yin Yap, the Lead for clinical health psychology and Bernie Byrne, the interim Macmillan lead nurse for cancer, set up a project of reaching out and supporting families and carers bereaved during this time.